Quantitative analysis of Glycyrrhizic acid from a polyherbal preparation using liquid chromatographic technique. - Amit K De; S Datta; A Mukherjee (Wolters Kluwer Medknow Publications, 2012)
Glycyrrhizic acid has been used in Indian traditional medicine for ages. It is obtained from the root extract of Glycyrrhizaglabra. There is seasonal variation of Glycyrrhizic acid content in the roots of the plant. So a proper method for quantification of the same is necessary from the polyherbal preparation available in the market. A simple, rapid, sensitive and specific reverse phase high performance liquid chromatographic method have been developed for the quantitative estimation of glycyrrhizic acid from polyherbal preparation containing aqueous root extract of Glycyrrhizaglabra using a photodiode array detector. The identity confirmation was carried out using mass spectrometry. Baseline resolution of the glycyrrhizic acid peak was achieved on a reverse phase C18 column (125 mm Ã- 4.0 mm, 5 Î¼) using an isocratic mobile phase consisting of 5.3 mM phosphate buffer and acetonitrile in the ratio 65:35 v/v. Chromatograms were monitored at 252 nm.5.3 mM phosphate buffer was replaced with 0.5mM ammonium acetate buffer in the mobile phase when MS detector was used. The method was found to be linear in the concentration range of 12.4 to124 Î¼g/ml with a correlation co-efficient of 0.999. The limit of detection and the limit of quantitation were 3.08 Î¼g/ml and 10.27 Î¼g/ml respectively. The average recovery from three spike levels was 99.93 Â± 0.26%. Identity confirmation of the chromatographic peak was achieved by electrospray ionization mass spectrometry and similar molecular ion peak was obtained for both sample and standard. The developed method is suitable for the routine analysis, stability testing and assay of glycyrrhizic acid from polyherbal preparations containing aqueous extracts of Glycyrrhizaglabra.